1368. Species Diversity and Co-Occurrence Patterning in Bone and Soft Tissue Infections. (4th December 2021) - Mindru, Cezarina; Rodriguez-Barradas, Maria; Bidare, Deeksha; Dudenhoeffer, Jan-Hendrik; Crawford, Kerri; Barshes, Neal R
Abstract: Background: Polymicrobial results from conventional cultures in bone and soft tissue infections have generally been reported as independent co-occurrences (i.e. assuming no relationship or interaction between species). The objective of this study was to identify non-random (dependent) co-occurrence in bone and soft tissue infections. Methods: We used single center Theradoc (Premiere Inc., Charlotte, NC) data on microbiology specimens collected over a decade (4/2010 to 4/2020). We included only tissue, fluid and swab specimens identified as being obtained from bone, skin, soft tissue or a wound during a patient's first episode of infection. Blood and liver biopsy specimens were excluded. Patterning involving >2 organisms was examined with factor analysis. Analyses were done with R version 3.6.1. Threshold p-values were adjusted for multiple comparisons, often to p< 0.001. Results: Polymicrobial culture results were seen much more frequently in the foot (76%) and sacrum (78%) than specimens from other locations (43%). The highest Shannon diversity index was seen in sacral specimens, followed by foot and leg specimens. Pseudomonas aeruginosa and E. coli was found more frequently in sacral bone and soft tissue specimens, while S. aureus was found most often in the spine bone and foot bone and soft tissue. Corynebacterium was found more frequently in foot bone (23%) and foot soft tissue (18%) than in non-foot soft tissue specimens (11%). Analysis of pairwise species co-occurrences in foot specimens (n=765) demonstrated that S. aureus made significantly less frequent the presence of Bacteroides, Enterobacter, and other staphylococcal species (Table 1). Analysis of non-foot soft tissue specimens (n=2, 647) confirmed this pairwise associations and suggested three patterns (Table 2): A, polymicrobial without S. aureus ; B, Enterococcus + gram negatives; and C, streptococcal. Table 1. Pairwise co-occurrences between species in bone and soft tissue specimens from foot infections (n=765). Factor analysis results demonstrating species associated with three polymicrobial patterns in soft tissue infection specimens. Blue denotes positive association (more often occurring as part of the pattern), red or grey denotes negative associations (less often occurring as part of the pattern). Numbers denote factor weights, a measure of the strength of the association. Conclusion: Species incidence and diversity vary by location and tissue type. The many non-random occurrences found suggest complex interrelationships between microbes in soft tissue and bone infections, including organisms often classified as non-pathogens. Further study may further characterize these relationships and aid in antibiotic selection. Disclosures: All Authors : No reported disclosures